Neurokinin 3 Receptor and Phosphocholine Transferase: Missing Factors for Pathogenesis of C-Reactive Protein in Preeclampsia. Issue 2 (February 2015) - Parchim, Nicholas F.; Wang, Wei; Iriyama, Takayuki; Ashimi, Olaide A.; Siddiqui, Athar H.; Blackwell, Sean; Sibai, Baha; Kellems, Rodney E.; Xia, Yang
Abstract : C-reactive protein (CRP), an innate immune mediator, is elevated in the circulation before symptoms in patients with preeclampsia, a severe hypertensive pregnancy disorder with high mortality and morbidity. However, the specific sources underlying increased CRP and the role of elevated CRP in preeclampsia are undefined. Here, we report that circulating CRP levels are significantly increased in a large cohort of normotensive pregnant individuals when compared with nulligravid women and is further increased in patients with preeclampsia. These findings led us to discover further that placental syncytiotrophoblasts are previously unrecognized cellular sources of CRP and underlie elevated CRP in normotensive pregnant women and the additional increase in patients with preeclampsia. Next, we demonstrated that injection of CRP induces preeclampsia features, including hypertension (157 mm Hg CRP treated versus 119 mm Hg control), proteinuria (35.0 mg/μg CRP treated versus 14.1 mg/μg control), kidney, and placental damage and increased levels of sFlt-1 in pregnant mice but not in nonpregnant mice. Our study implicates that phosphocholine transferase, a placental-specific enzyme post-translationally modifying neurokinin B, is essential for the pathogenic role of CRP in preeclampsia through activation of the neurokinin 3 receptor. Overall, our studies have provided significant new insight on the pathogenic role of CRP in preeclampsia and highlighted innovative therapeutic strategies. Abstract : Supplemental Digital Content is available in the text.